A novel uniplanar broadband antenna using coplanar stripline and epsilon negative transmission line. Issue 7 (31st August 2018) - Zhang, Xiao‐Fei; Wang, Guang‐Ming; Liang, Jian‐Gang; Zong, Bing‐Fen
Abstract: A novel uniplanar broadband antenna using the coplanar stripline (CPS) and the epsilon negative transmission line (ENG TL) is presented in this article. By using CPS as the feeding structure, the antenna becomes more compact in the transverse direction and the uniplanar structure makes it easier to integrate with other microwave components. By integrating ENG TL on the antenna, the zeroth‐, first‐, and second positive‐order resonant modes located at 3.50 GHz, 5.72 GHz, and 6.57 GHz, respectively, have appeared. The bandwidth enhancement is achieved due to that the three resonant modes of the ENG TL are merged into a wideband with good impedance matching. Simulation and measured results have shown that the bandwidth of the proposed antenna is increased from 1.95 GHz (4.58 GHz ∼ 6.53 GHz) to 3.47 GHz (3.26 GHz ∼ 6.73 GHz) compared with its unloaded counterpart.